2017
DOI: 10.1016/j.ijfoodmicro.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Yeast community in traditional Portuguese Serpa cheese by culture-dependent and -independent DNA approaches

Abstract: This study investigated the yeast community present in the traditional Portuguese cheese, Serpa, by culture-dependent and -independent methods. Sixteen batches of Serpa cheeses from various regional industries registered with the Protected Designation of Origin (PDO) versus non-PDO registered, during spring and winter, were used. Irrespective of the producer, the yeast counts were around 5log CFU/g in winter and, overall, were lower in spring. The yeast species identified at the end of ripening (30days), using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 47 publications
7
33
1
Order By: Relevance
“…Apart from assimilating sugars and lactic acid, the yeast is supposed to hydrolyse lipids and proteins and to inhibit the formation of biogenic amines, which has a positive influence on the taste of the final product (Grygier et al 2017). C. cabralensis has been isolated from Spanish blue-veined Cabrales cheese and from Portugese Serpa cheese (Flórez et al 2010; Gonçalves Dos Santos et al 2017). In fact, our study is the first documented isolation of this yeast from another source than cheese.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from assimilating sugars and lactic acid, the yeast is supposed to hydrolyse lipids and proteins and to inhibit the formation of biogenic amines, which has a positive influence on the taste of the final product (Grygier et al 2017). C. cabralensis has been isolated from Spanish blue-veined Cabrales cheese and from Portugese Serpa cheese (Flórez et al 2010; Gonçalves Dos Santos et al 2017). In fact, our study is the first documented isolation of this yeast from another source than cheese.…”
Section: Resultsmentioning
confidence: 99%
“…K . marxianus is also found frequently in young or short‐ripened cheeses (Cardoso et al, ; Ceugniez, Drider, Jacques, & Coucheney, ; Goncalves Dos Santos, Benito, de Guia Cordoba, Alvarenga, & Ruiz‐Moyano Seco de Herrera, ) as well as in yellow‐type acid‐curd cheeses (Bockelmann, ).…”
Section: Role Of Yeasts In Cheese Ripeningmentioning
confidence: 99%
“…HTS analysis of this fungal community of both PDO and non-PDO forms of Serpa cheeses, highlighted diversity among the yeasts present in a manner suggested that production practices and the associated environment have a considerable influence on the final yeast population. Through these investigations it was possible to alter ripening conditions to favor the dominance of yeast species that are desirable for optimal Serpa production (Gonçalves Dos Santos et al, 2017 ). Another ewe's milk cheese produced by traditional techniques without starters, in this case from Croatia, has also been the subject of HTS-based analysis.…”
Section: Identification Of Factors Influencing the Development Of Thementioning
confidence: 99%
“…There have been a number of research and review papers dedicated to describing methodologies used for sequencing (Di Bella et al, 2013 ) work flow, limitations, applications to dairy foods (Ercolini, 2013 ; Walsh et al, 2017 ), comparing sequencing platforms, and bioinformatics pipelines as well as highlighting pros and cons associated with all of the above (Kelleher et al, 2015 ; Clooney et al, 2016 ; Walsh et al, 2018 ) Depending on sequencing depth, HTS can facilitate the detection of taxa present at low levels, a feature of great value in the context of testing for spoilage or pathogenic microbes. HTS technology can also be employed to study the microbial diversity of protected designation of origin (PDO) cheeses to establish which components are responsible for the authentic taste, flavors, and textures of these products (Alegría et al, 2012 ; Fuka et al, 2013 ; De Filippis et al, 2014 ; Delcenserie et al, 2014 ; De Pasquale et al, 2014 , 2016 ; Riquelme et al, 2015 ; Dalmasso et al, 2016 ; Parente et al, 2016 ; Giello et al, 2017 ; Gonçalves Dos Santos et al, 2017 ; Li et al, 2017 ). The same technology could, in the future, be employed to establish authenticity.…”
Section: Introductionmentioning
confidence: 99%